Relative Bioavailability of Enalapril Administered as Orodispersible Minitablets in Healthy Adults. Issue 2 (14th August 2019) - Van Hecken, Anne; Burckhardt, Björn B.; Khalil, Feras; de Hoon, Jan; Klingmann, Ingrid; Herbots, Marissa; Laeer, Stephanie; Lagler, Florian B.; Breitkreutz, Jörg
Abstract: The angiotensin‐converting enzyme inhibitor enalapril is commonly used to treat chronic heart failure in children. Because some children are unable to swallow capsules or tablets, a new, age‐appropriate, orodispersible minitablet (ODMT) containing 1 mg of enalapril was developed within the EU‐funded LENA (Labeling of Enalapril from Neonates up to Adolescents) consortium. In order to support the clinical evaluation of this new formulation in children, a relative bioavailability study was performed in healthy adults, comparing the bioavailability of enalapril in the ODMT with that of a reference product (RP) Renitec, a registered standard enalapril tablet formulation. In this open‐label, randomized 3‐way crossover study, 24 healthy subjects received a 10‐mg enalapril dose administered as (1) 2 × 5‐mg tablets of the RP swallowed with water, (2) 10 × 1‐mg ODMT swallowed with water, and (3) 10 × 1 mg ODMT dispersed on the tongue. When the relative bioavailability of the ODMT formulation swallowed with water was compared with that of the RP, the estimated 90%CIs for the ratio of area under the concentration‐time curve (AUC0‐∞ ) and or peak concentration (Cmax ) of enalapril were 92.34% to 106.49% and 91.28% to 115.72%, respectively, which are within the accepted bioequivalence limits of 80% to 125%. Following dispersion of the ODMT in the mouth, a slightly higher Cmax for enalapril was observed as compared with the RP with an upper 90%CI of 127.57%, slightly exceeding the bioequivalence limit. Taken together, it was demonstrated that the method of administration of the ODMT, swallowed or dispersed, did not significantly affect the bioavailability of enalapril.